Comparative Analysis of The Application of Leadership Style in Pondok Pesantren, Madrasah, and Schools - Ismail, Ismail; Sukoco, Sugeng; Mesiono, Mesiono; Herianto, Herianto (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study aims to analyze the differences (comparations) in the application of leadership styles in Islamic boarding schools, madrasas, and schools. The background of this research includes a multi-site study, namely at the Musthafawiyah Islamic Boarding School, MAN 1 Sibolga, and SMPN 1 Sibolga. This type of research uses a qualitative approach with a comparative study method. Where, the researcher attempts to describe the problem of events through respondents or other data sources related to the leadership style at Pesantren Musthafawiyah (Mandailing Natal), MAN 1 Sibolga, and SMPN 1 Sibolga, then a comparison of leadership styles at the three educational institutions is made. The results of this study indicate that the application of the leadership style of Islamic boarding schools is different from the leadership style in madrasas and schools. This is because the leadership style of pesantren tends to be laissez faire and authoritarian based on the charismatic kyai (Islamic boarding school leader). While in schools and madrasas apply a democratic leadership style.